Estructura y germinación de las semillas de Bixa orellana L. (achiote) - Rivera, Dora I. (1983)
Ovules of Bixa orellana L. are crassinucellate, bitegmic and have a micropyle formed by both integuments. Ovular position varies during development. Survival of the chalazal m egaspore results in monosporic gametophyte. Fertilization is porogamous, and syngamy and triple fusion seem to occur simultaneously. The proembryo seems to be a massive coenocyte; later, it becomes cellular. The embryo is spatulate and the radicle is antitropous. Germination takes place through a chalazal canal next to the hilum. The outer integument contains the pigment bixine.